An efficient multi channel, 0.2 nJ/bit transmitter with tuning for process variation for biomedical telemetry in the MedRadio band of 401-457MHz - Gundla, Abhiram Reddy, author; Chen, Tom, advisor; Collins, George, committee member; Henry, Chuck, committee member (Colorado State University. Libraries, 2016)
With the increasing applications of bio-integrated telemetric systems, there is a growing demand for wireless transceivers in these systems to interface with the outside world. The use of wireless transceivers is desirable because they allow complete untethering of medical devices from patients. Applications of the medical devices that have transceivers may include, but not limited to, neuro-prosthetics for stimulation, sensing vital signs, wireless monitoring of neuro chemicals in the brain, wireless endoscopy, and remote medical diagnosis and therapy. The implantable medical devices to introduce impulses to the central nervous system to treat the diseases efficiently and/or to provide relief to pain are usually in the medical implantable communication services band of 401-406 MHz. The spectrum of 401-457 MHz band is called medical device radio communications service (MedRadio) band, was allocated by FCC on secondary basis. There exists various transmitter designs for the MedRadio band aimed at high energy efficiency (i.e. low energy per bit transmitted), as low as 0.16 nJ/bit. A few designs are targeted to work at high dc power transmission efficiency, as high as 22%. But, the existing designs fail to be truly MedRadio-standard complaint with short-comings either in terms of not using all the channels in the MedRadio band, low transmitter efficiency, or low output power emitted. The search for better designs of transmitters that can utilize all the channels with high transmission efficiency and high emitted output power continues. This thesis proposes an efficient multichannel transmitter circuit design in the MedRadio band at 401-457 MHz. The transmitter circuit consists of a multichannel phase locked loop (PLL) with rail to rail quadrature output voltage controlled oscillator (VCO), a low power digital synchronous programmable integer N-divider, bang bang Phase frequency detector (PFD), charge pump and a 3rd order loop filter, a passive mixer and a power amplifier (PA). The VCO of the transmitter is designed to account for process variation. The proposed transmitter uses quadrature phase shift keying (QPSK) modulation scheme to transmit data. The power consumption of the transmitter is 460 µW at the power supply voltage of 1.2 V, and consumes only 0.2 nJ of energy for every bit transmitted in the MedRadio band. The output power emitted by the power amplifier of the transmitter is -10.8 dBm. The transmitter is able to hop through all the 10 channels of 300 kHz bandwidth of each from 402 to 405 MHz, all the 4 channels of 6MHz bandwidth of each from 413 to 457 MHz. The overall global efficiency of the transmitter is 13.9 %. The proposed transmitter meets all the FCC requirements for the MedRadio band. This proposed work is implemented in a 180nm CMOS process. The proposed transmitter working in the MedRadio band consumes only 0.2 nJ/bit compared to 0.65 nJ/bit of the only other MedRadio-band compliant design. The transmitter energy consumption is low at 460 µW and efficiency is high at 13.9% when compared to mW energy consumption and single-digit efficiency achieved by existing designs.
Keywords: MICS; PLL; transmitter; MMNs; MedRadio band; QPSK